Electronic structure measurement of solid density plasmas using x-ray scattering - Gregori, G; Glenzer, S; Rogers, F; Landen, O; Blancard, C; Faussuriei, G; Renaudin, P; Kuhlbrodt, S; Redmer, R (2004)
We present an improved analytical expression for the x-ray dynamic structure factor from a dense plasma which includes the effects of weakly bound electrons. This result can be applied to describe scattering from low to moderate Z plasmas, and it covers the entire range of plasma conditions that can be found in inertial confinement fusion experiments, from ideal to degenerate up to moderately coupled systems. We use our theory to interpret x-ray scattering experiments from solid density carbon plasma and to extract accurate measurements of electron temperature, electron density and charge state. We use our experimental results to validate various equation-of-state models for carbon plasmas.